Perception of the surgeon-dentist regarding the use of informed Consent in dental treatment - Saliba Garbin, Cléa Adas; Isper Garbin, Artênio José; Anjos Santos, Cleide dos; Gonçalves, Patrícia Elaine (Acta Bioethica, 2009)
The objective of this study was to evaluate: the profile of the surgeon-dentist that undergoes a course in specialization at the Odontology Faculty of Aracatuba/UNESP, Brazil; if they requested informed consent from the patient and/or their legal representative before the realization of procedures, and if the treatment was decided upon with the patient. It was elaborated, validated and applied in questionnaire form, and the data obtained was analyzed by the program EPI-INFO 3.3 The conclusion was, given that surgeon-dentists still do not obtain any type of document before beginning treatment, a large percentage of them are totally vulnerable if submitted to ethical or legal prosecution and that it is necessary to be aware of this aspect.